Respon Bioakumulator Eceng Gondok (Eichhornia crassipes) Terhadap Logam Berat Pb dan Cd di Sungai Pegangsaan Dua - Rahayu, Sri Teguh; Faradilla, Meutia; Verawati, Ester Yani; Triana, Muchrip (Pharmaceutical Sciences and Research, 2014)
Eichhornia crassipes is one of Indonesia’s wild plant that considered as weed. Its presence can disrupt ecosystems in the river. However, it is proven to absorb Pb and Fe. It is also believed that E.crassipes can absorb other metals such as Hg , Zn , Cu and Cd which were belong to the same group as Pb and Fe. In addition to heavy metal sequestration, Eichhornia crassipes can also absorb pesticide residues. This descriptive research was done to determine the bioaccumulator response to Pb and Cd in Pegangsaan Dua river using Inductively Coupled Plasma method. Bioaccumulator response of Eichhornia crassipes were analyzed from the stem. The results of the study also showed that the Eichhornia crassipes plants were able to accumulate heavy metals of Pb and Cd. The organs most potential to absorb Cd and Pb were stem organ with average point 1 of Cd : 0,056 ppm and Pb : 0,5002 ppm, then the average point 2 of Cd : 0,0328 ppm and Pb : 0,0215 ppm , and the average point 3 of Cd : 0.0143 ppm and Pb : 1,293 ppm . In this end, it is suggested that the stem organ could be developed as bioaccumulation agent.